Ab Initio Language Teaching in British Higher Education The Case of German - Bavendiek, Ulrike; Mentchen, Silke; Mossmann, Christian; Paulus, Dagmar (Advances in Language Education, 2022)
Drawing extensively on the expertise of teachers of German in universities across the UK, this volume offers an overview of recent trends, new pedagogical approaches and practical guidance for teaching at beginners level in the higher education classroom. At a time when entries for UK school exams in modern foreign languages are decreasing, this book serves the urgent need for research and guidance on ab initio learning and teaching in HE. Using the example of teaching German, it offers theoretical reflections on teaching ab initio and practice-oriented approaches that will be useful for teachers of both German and other languages in higher education. The first chapters assess the role of ab initio provision within the wider context of modern languages departments and language centres. They are followed by sections on teaching methods and innovative approaches in the ab initio classroom that include chapters on the use of music, textbook evaluation, the effective use of a flipped classroom and the contribution of language apps. Finally, the book focuses on the learner in the ab initio context and explores issues around autonomy and learner strengths. The whole builds into a theoretically grounded guide that sketches out perspectives for teaching and learning ab initio languages that will benefit current and future generations of students.